A colonização agroindustrial do cerrado em Mato Grosso (1970-2000) - Cruz, Paulo Divino Ribeiro da [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
This thesis investigates the environmental changes occurring within the Cerrado of Mato Grosso induced agro-industrial colonization in the period between the early 1970s and 2000. Their main goal is to demonstrate that natural, traditional and subsistence agroecosystems were supplanted by capitalistic agroecosystem implying harmful to the natural environment and exacerbating social and economic contradictions. Analyzes the agroecosystems of Mato Grosso Brazilian savanna on the threshold of the 1980s; we show the regional inequalities arising from agro-industrial occupation; investigates the role of agricultural research in the conquest and development of the Brazilian savanna deployed from 1970s model, considering the impacts of special development programs implemented in the region by the federal government and the state government. It is concluded that as a result of this colonization process agribusiness, Mato Grosso has been transformed into an area of production of raw materials, food and fiber for the contemporary stage of industrialization of the core countries while consumption area of capital and technologies produced those countries where it originated the development model implemented here

Esta tese investiga as transformações socioambientais ocorridas no Cerrado mato-grossense induzidas pela colonização agroindustrial a partir do início da década de 1970 até ano 2000. Seu objetivo é demonstrar que os sistemas agroecológicos naturais, tradicionais e de subsistência foram suplantados pelo sistema agroecológico capitalista, implicando em efeitos danosos para o ambiente natural e acirrando as contradições sociais e econômicas. Analisam-se os sistemas agroecológicos do Cerrado mato-grossense no limiar dos anos 1980; demonstram-se as desigualdades regionais oriundas da ocupação agroindustrial; investiga-se o papel da pesquisa agropecuária na conquista do Cerrado e o modelo de desenvolvimento implantado a partir dos anos 1970, considerando os impactos dos programas especiais de desenvolvimento implantados na região pelo governo federal e pelo governo estadual. Conclui-se que, como resultado desse processo de colonização agroindustrial, Mato Grosso foi transformado em uma área de produção de matérias primas, alimentos e fibras para a etapa de industrialização contemporânea dos países centrais e, ao mesmo tempo, área de consumo de capitais e tecnologias produzidas por aqueles países de onde se originou o modelo de desenvolvimento aqui implantado
Keywords: Colonização agraria; Agroindústria; Cerrados; Meio ambiente; History; Mato Grosso - História